Longtail tuna fisheries in the northern Arabian Sea off the north-west coast of India: Moving towards developing spatially explicit fisheries management strategy - Koya, K. Mohammed; Rrohit, Prathibha; E. M., Abdussamad; Vase, Vinay Kumar; A. P., Dineshbabu (Indian Journal of Fisheries, 2018)
Longtail tuna (Thunnus tonggol, Bleeker, 1851), the largest growing species among neritic tunas have a unique distribution pattern globally. Northern Arabian Sea together with the Oman Sea and Persian Gulf in the north-western Indian Ocean is considered to be the major area where the species is abundant and form sizeable fisheries globally. India has an artisanal tuna fishery and contributes nearly 10% of the longtail tuna landing in the region, with Gujarat alone contributing nearly 80%. The paper updates on the longtail tuna fisheries in the region with focus on the north-west coast of India together with its spatial characteristics. Clues on the areas of abundance of the species along Gujarat coast over the seasons and temporal movements of different ontogenetic stages in the shelf areas are revealed. The study sets prelude to a cost effective and participatory collection of spatially referred data on the artisanal and small scale fisheries in the region.